Miracle at St. Anna [videorecording (DVD)] - Luke, Derek, 1974-; Ealy, Michael; Alonso, Laz; Turturro, John, 1957-; Leguizamo, John; Washington, Kerry, 1977-; McBride, James, 1957- (Touchstone Home Entertainment, 2009)
August 1944. Follows four black soldiers of the all-black 92nd Infantry Division who get trapped near the small Tuscan village of Sant'Anna di Stazzema on the Gothic Line during the Italian Campaign of World War II. One of the men will risk his life to save an Italian boy who lives in the city where the Waffen-SS have massacred most of the citizens of the town in retaliation for Italian partisan activity. A sculpted head from the Ponte Santa Trinita in Florence is a focal point.